KARAKTERISTIK HABITAT DAN PENYEBARAN KULIM (Scorodocarpus borneensis Becc.) DI HUTAN LARANGAN ADAT RUMBIO - Khalid Afif; Defri Yoza; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Kulim (Schorodocarpus borneensis Becc.) is the multipurpose tree species(MPTS), almost the part of tree can be used at this time, although most economic value is wood. Kulim is one of the species that already rare the forest. The aims of this research was to determine the characteristic of kulim in the prohibition tradition Rumbio forest and the distribution of kulim from the seedlimg and it is habitat. This research was conducted in March-April 2016 in the prohibition Rumbio forest. This research using primary data and secondary data. The data collect from systematic sampling with random start technic and plot sizing 50 m x 50 m using purposive sampling technique. Kulim has a habitat on sandy loam, yellowish brown, average water content 5,88% with pH 5,40 (acid). Kulim is located at altitude 93 mdpl-103 mdpl. Average temperatures 25,71 ˚C and average humidity 71,46 %, the thickness of the litter 45 cm. Total of the species 32, Shorealeprosula higher 22,32 INP.Macaca nemestrina, Tupaia javanica, Sus scrofa,Hebarctus malayus and Neofelis nebulosa is the species of animal can be found and can indentify around kulim. Parent tree can be found in the prohibition traditional Rumbio as much as 5 individuals from five lines. Regeneration of kulim for seedlings found 60 individuals farthest distance seedlings from parent tree 1015 cm and the closest distance 57 cm. Keywords : Spread, Habitat, Kulim, Prohibition Rumbio Forest.